2009
DOI: 10.1007/s00246-009-9441-2
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide as an Adjunctive Diagnostic Test in the Acute Phase of Kawasaki Disease

Abstract: Coronary arteritis rather than myocardial involvement is typically emphasized in Kawasaki disease (KD). Moreover, the criteria and the usual biological markers oversee the importance of cardiac-specific markers in diagnosing this disease. We sought to study the clinical usefulness of measuring B-type natriuretic peptide (BNP) and its N-terminal moiety (NT-proBNP) at the onset of KD. Our objective was to evaluate blood concentrations of BNP and NT-proBNP during the acute and subacute phases of KD. We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 43 publications
3
85
2
Order By: Relevance
“…diffuse fibrosis or local scarring in regions of myocardial, ischemia or infarct (Takahasi, 1989;Dahdah, 2009). KD-associated inflammatory damage can potentially affect all of the components of the cardiovascular system and even other bodily areas as a consequence of vasculitis; thus, systematic follow-up is necessary until adult age in all children who have had this disease, even when his/her manifestations have not been severe, and especially in these children who manifested myocarditis without coronary artery injuries, because to date we do not know the characteristics and long-term consequences of this particular problem.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…diffuse fibrosis or local scarring in regions of myocardial, ischemia or infarct (Takahasi, 1989;Dahdah, 2009). KD-associated inflammatory damage can potentially affect all of the components of the cardiovascular system and even other bodily areas as a consequence of vasculitis; thus, systematic follow-up is necessary until adult age in all children who have had this disease, even when his/her manifestations have not been severe, and especially in these children who manifested myocarditis without coronary artery injuries, because to date we do not know the characteristics and long-term consequences of this particular problem.…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenesis of these myocardiac injuries and their consequences in the long term with respect to the heart are little understood to date and should not be underestimated; thus, it is necessary to establish methodological follow-up patterns in these patients. The possibility has also been set forth of reclassifying the clinical signs and other findings regarding left ventricle dysfunction in KD (Gordon, 2009;Dahdah, 2009). …”
Section: Myocarditismentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with cardiomyocyte stress, markers of inflammation, oxidative stress, and echocardiographic measurements. Presence of NT-proBNP suggests diastolic dysfunction (28). Some researchers propose that NT-proBNP may be an excellent biomarker for supporting the diagnosis of KD (29).…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…All found significant diagnostic values for KD as shown in Table 1. Dahdah et al reported a clear advantage of NT-proBNP over BNP indicating superiority as a diagnostic biomarker in KD (7). This might be due to different half-lives of BNP and NT-proBNP (20-30 minutes versus 60-120 minutes, respectively).…”
mentioning
confidence: 99%